On the use of the SF6 gas tracer technique in Latin America for measuring methane emissions in ruminants : a review and analysis - Loza, Cecilia; Ceron Cucchi, Maria Esperanza; Cabezas-Garcia, Edward Hernando; Ortiz Chura, Abimael; Gualdrón-Duarte, Laura Bibiana; Gere, José Ignacio (Taylor and Francis, 2024)
The SF6 gas tracer technique is extensively used to measure enteric CH4 emissions for scientific research in Latin-American countries. Although guidelines on how to properly implement this technique have been published, its use has been the subject of considerable uncertainty due to a high variation within measurements when compared to results obtained with other techniques. Therefore, a detailed evaluation of this technique is important to identify the main sources of variability. The aim of this study is to summarise the key factors contributing to this variation, as reported in studies conducted in Latin America (LA). The final dataset comprised 63 studies and the variables considered within our analysis were split into two main categories: (1) Production systems and animal-related factors driving enteric CH4 emissions and (2) Aspects related to the implementation of the SF6 gas tracer technique in research laboratories, such as: duration of the collection period, and mean permeation rate of the SF6 collection canisters, among others. The lack of specific details regarding the SF6 gas tracer technique in the compiled dataset from LA studies is notable. Despite this, the main sources of variation identified were related to both the duration of the sampling period and the SF6 permeation rate.